In search of the Holy Grail: Poisons and extended release local anesthetics. Issue 1 (March 2019) - Coppens, Steve J.R.; Zawodny, Zoriana; Dewinter, Geertrui; Neyrinck, Arne; Balocco, Angela Lucia; Rex, Steffen
Abstract : Regional anesthesia has been advocated as adjunct to a multimodal analgesia regimen. The limited duration of the action of available local anesthetics limits their application. Catheters, perineural or IV adjuvants, or repetition of blocks are modalities available to prolong the analgesic benefit of LRA. All of these approaches have their shortcomings. New extended release local anesthetic formulations may provide time-efficient and longer duration of analgesia with a single injection. Available data on liposomal bupivacaine are promising, and more recently, it has been FDA approved for use in interscalene brachial plexus block but not for other nerve blocks at this time. Several other new formulations and compounds, such as HTX-011, Neosaxitoxin, and SABER-Bupivacaine, are also being developed and tested for their safety and analgesic potential.